Edukasi Mengenai Pencegahan dan Pengobatan Schistosomiasis di Desa Dodolo Lore Utara - Handayani, Tien Wahyu; Tandi, Joni; Putri, Debby Aulia; Ticoh, Febriyani; Rusdi, Grasela; Uigianto, Imelda; Ahmad, Mirnawati; Safitri, Nabila Umi (Prima Abdika: Jurnal Pengabdian Masyarakat, 2025)
Schistosomiasis is an infectious parasitic disease caused by the Schistosoma worm, transmitted by the snail Oncomelania hupensis lindoensis in endemic areas such as Dodolo Village, Poso Regency, Central Sulawesi. This village has the highest number of intermediate snail foci in the Napu highlands, making it a strategic location for educational interventions. This community service activity aims to improve community knowledge, attitudes, and behavior related to the prevention and treatment of schistosomiasis. Education was carried out using interactive lecture methods, discussions, and pre-test and post-test evaluations of 34 participants from various levels of society. The results showed an increase in the average knowledge score from 3.76 (37.6%) in the pre-test to 8.00 (80.0%) in the post-test, with increased participation and overall understanding. This activity succeeded in building collective awareness and understanding that was evenly distributed throughout the community, and was responded to with a high level of satisfaction (92%). It can be concluded that the participatory education approach is effective in increasing the capacity of the Dodolo Village community in controlling schistosomiasis and can be replicated in other endemic areas as part of a national elimination strategy.